The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/jvp.12008
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of cytarabine in dogs when administered via subcutaneous and continuous intravenous infusion routes

Abstract: This crossover study compared the pharmacokinetics of cytarabine in six healthy dogs following intravenous constant rate infusion (CRI) and subcutaneous (SC) administrations, as these are two routes of administration commonly employed in the treatment of meningoencephalitis of unknown etiology. Each dog received a SC cytarabine injection of 50 mg/m(2) or an 8 h CRI of 25 mg/m(2) per hour, with a 7-day washout before receiving the alternative treatment. Blood samples were collected for 16 h after CRI initiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(65 citation statements)
references
References 18 publications
(20 reference statements)
5
60
0
Order By: Relevance
“…The C max , T max , half‐life (T 1/2 ), area under the concentration versus time curve (AUC), and clearance averages for each dose are presented in Table . The T 1/2 of Ara‐C in this study ranged from 1.4–1.6 hr, which is similar to previous reports (Crook et al, ; Pastina et al, ; Scott‐Moncrieff et al, ). A single 200 mg/m 2 injection resulted in the greatest overall drug exposure (AUC) at 32,510 ng × hr/ml, with a linear relationship between dose and AUC (Figure ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The C max , T max , half‐life (T 1/2 ), area under the concentration versus time curve (AUC), and clearance averages for each dose are presented in Table . The T 1/2 of Ara‐C in this study ranged from 1.4–1.6 hr, which is similar to previous reports (Crook et al, ; Pastina et al, ; Scott‐Moncrieff et al, ). A single 200 mg/m 2 injection resulted in the greatest overall drug exposure (AUC) at 32,510 ng × hr/ml, with a linear relationship between dose and AUC (Figure ).…”
Section: Resultssupporting
confidence: 92%
“…Cytarabine (Ara‐C) is an antimetabolite that is rapidly deaminated to an inactive metabolite and also phosphorylated to an active form which is then incorporated into DNA resulting in inhibition of DNA polymerase (Crook et al, ; Rustum & Raymakers, ; Seymour, Huang, & Plunkett, ). It is approved for intravenous (IV), subcutaneous (SQ), and intrathecal administration (Fischer, Knobf, & Durivage, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the limitations of this small study, we are able to conclude that the drugs commonly used in the treatment of MUE do not appear to alter the C MAX and AUC of CA delivered by CRI. Additionally, our findings for C MAX and AUC values obtained after a CRI of CA alone in the population of dogs diagnosed with MUE are lower than those of healthy beagle dogs (Crook et al ., ). These results may be due to differences in diseased vs. healthy dogs, or due to differences in sampling time points, as the beagle dogs were sampled intensively and up to 16 h after the infusion was initiated, whereas the clinical population of dogs was sampled up to 12 h and sparsely.…”
Section: Pharmacokinetic Parameters For Ca and Multiple Drug Therapiementioning
confidence: 97%
“…A pharmacokinetic study comparing subcutaneous bolus administration versus intravenous infusion revealed that based on Fick's first law of diffusion, intravenous infusion may produce a more prolonged exposure of cytosine arabinoside at cytotoxic levels in plasma in comparison with the concentrations after subcutaneous administration. 161 However, further study in dogs with MUO is needed to identify whether the sustained concentrations produced by intravenous infusion would improve penetration of cytosine arabinoside across the BBB and produce higher efficacy for the treatment of MUO. Alternative approaches include prolonged use of oral leflunomide or cyclosporine in combination with prednisone tapered over approximately 6 to 12 weeks.…”
Section: Treatmentmentioning
confidence: 99%